Moving beyond the Influence of Neighbors on Policy Diffusion: Local Influences on Decisions to Conduct Property Tax Reassessment in New York - Eom, Tae Ho (2017)
Over the past few decades, research on policy adoption and diffusion has grown rapidly. Despite the relatively large number of publications, however, little attention has been paid to the important question of why a policy is differently implemented or diffused across governments. To answer this question and improve our understanding of local policy choice beyond widely cited neighboring influences, we closely examine the roles of three main policy actors—internal actors, external actors, and go-betweens—in the local policy diffusion process, drawing particularly upon property tax reassessment scenarios. In addition, we focus on nested institutional arrangements, including form of government and type of property tax assessor, that affect the policy decisions of internal actors. Using data on cities and towns in New York State for 1993-2010, we estimate event history models of property tax reassessment activities. Our findings reveal that regional interactions with neighbors that have already adopted the policy and top-down go-betweens through positive inducements can help facilitate property tax reassessment across municipalities. Reformed municipal governments in the council-manager form, along with appointed assessors, are also most likely to adopt reassessment policy frequently, compared with other institutional arrangements. Overall, this study advances the policy diffusion literature by exploring the roles of different influences through a more detailed, broader approach.